Effectiveness of Cognitive Behavioral Couple Therapy Based on Heimberg's Model on Sexual Schemas and Sexual Satisfaction of Distressed Women - Saeedi, Hamed; Molazadeh, Alireza; Heidari, Hasan; Davoodi, Hossein (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: The present study aimed to evaluate the effectiveness of cognitive behavioral couple therapy based on Heimberg's model on sexual schemas and sexual satisfaction among distressed women.Methods and Materials: This applied research employed a quasi-experimental design with a pretest-posttest and control group format. The statistical population included all distressed women referred to counseling and psychology clinics in Karaj in 2023. A purposive non-random sampling approach selected 30 participants, who were randomly assigned into two groups (15 in the experimental group and 15 in the control group). Assessment tools included the Sanaei Marital Conflict Questionnaire (1999), Anderson and Cyranowski’s Self-Sexual Schema Questionnaire – Women's Form (1994), and the Sexual Satisfaction Scale by Mattson and Trapnell (2005). The experimental group received cognitive behavioral couple therapy based on Heimberg's model in 12 sessions of 90 minutes each, held weekly. Data were analyzed using multivariate covariance analysis.Findings: The findings indicated a significant difference (p < .05) in the posttest means of sexual schema and sexual satisfaction between the experimental and control groups, after controlling for pretest effects.Conclusion: Thus, cognitive behavioral couple therapy based on Heimberg's model can be considered an effective treatment method for improving sexual schemas and enhancing marital sexual satisfaction among distressed women.